2015
DOI: 10.1039/c5an00864f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of low concentrations of ampicillin in milk

Abstract: Ampicillin, a common antibiotic, is detected at trace concentrations in milk using surface enhanced Raman spectroscopy in a microfluidic device, using less than 20 μL of sample, in 10 minutes, with minimal off-chip preparation. The device is configured so as to favor the interaction of the analyte with colloidal silver, and the optimization of the aggregation of the silver nanoparticles so as to increase the SERS intensity and the consequential sensitivity of analyte detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 15 publications
(18 reference statements)
1
24
0
Order By: Relevance
“…In Figure 6a, SERS spectra for ampicillin in milk solution with low concentration of 0.01 ppm (e.g., to meet a standard for the residue regulation), using Al 2 O 3 /, HfO 2 /, and TiO 2 /Ag HNS were demonstrated. Characteristic peaks at 1007, 1115, 1447, and 1594 cm −1 for ampicillin were still distinguishable [39]. It was also observed that there are peaks at 1300-1400 cm −1 due to the interactions between Di NPs and Ag or Ag-O surface, as previously discussed in Section 3.4 (i.e., Figure 5a-c).…”
Section: Nps/ag Hns For Trace Detection Of Ampicillin In Milk Solusupporting
confidence: 72%
See 2 more Smart Citations
“…In Figure 6a, SERS spectra for ampicillin in milk solution with low concentration of 0.01 ppm (e.g., to meet a standard for the residue regulation), using Al 2 O 3 /, HfO 2 /, and TiO 2 /Ag HNS were demonstrated. Characteristic peaks at 1007, 1115, 1447, and 1594 cm −1 for ampicillin were still distinguishable [39]. It was also observed that there are peaks at 1300-1400 cm −1 due to the interactions between Di NPs and Ag or Ag-O surface, as previously discussed in Section 3.4 (i.e., Figure 5a-c).…”
Section: Nps/ag Hns For Trace Detection Of Ampicillin In Milk Solusupporting
confidence: 72%
“…Among them, the peak at 1007 cm −1 is the most prominent peak. Note that milk is a complex fluid with an emulsion of suspended lipid droplets and a variety of sugars and proteins [39]. A lipid-removal procedure, as described in Experimental section, was thus necessarily prior to the sample into the detection [50,51].…”
Section: Nps/ag Hns For Trace Detection Of Ampicillin In Milk Solumentioning
confidence: 99%
See 1 more Smart Citation
“…Aswathy et al 13 have synthesized silver nanowires using the polyol process with ethylene glycol as a reducing agent and polyvinylpyrrolidone as a stabilizer, using a microwave technique. Andreou et al 17 reported a microuidic device to detect trace concentrations of ampicillin in milk using the aggregation of silver nanoparticles so as to increase the SERS intensity, only using less than 20 mL of sample, in 10 minutes, with minimal off-chip preparation. Zhang et al 10 demonstrated that the optical properties of Ag nanoplates can be precisely tuned over a wide range through a UV-light-induced reconstruction process, in which the morphology of the nanoparticles changes from thin triangular plates to thick round plates, and the effects of different ultraviolet wavelengths, irradiation times and polyvinylpyrrolidone (PVP) were investigated in synthesising silver nanosheets.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-Enhanced Raman Scattering (SERS) is capable of chemical sensing yet currently is performed either on chemicals that are adsorbed on a particular substrate, by scanning with a sharp metallic tip [ 1 , 2 ], or by dispersing metallic nanoparticles into the solution. The ability to analyze the composition of a mixture on the nanoscale makes the use of SERS substrates beneficial for environmental analysis, pharmaceuticals, material sciences, art and archeological research, forensic science, drug and explosives detection, food quality analysis [ 3 ], and single-algal cell detection [ 4 , 5 , 6 ]. SERS combined with plasmonic sensing can be used for a high-sensitivity and quantitative detection of bio-molecular interaction [ 7 ] and to study redox processes at the single molecule level [ 8 ].…”
Section: Introductionmentioning
confidence: 99%